PENGARUH KOMPOSISI LIDAH BUAYA ( Aloe vera), KULIT MANGGIS (Gracinia mangostana L.) DAN TEPUNG BERAS (Oryza sativa L.) SEBAGAI PELAPIS KERABANG TERHADAP KUALITAS INTERNAL TELUR AYAM RAS - Eewi Maulina Raninda, Dian Septinova, Khaira Nova, dan Riyanti (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2019)
The purpose of this research was to find out interior quality of 60 eggs laying hen coated by solution of Aloe vera, mangosteen peel solution (MPS), rice flour (RF) and stored during 14 days. This research carried out on December 2018 at the Animal Production and Reproduction Laboratory, Department of Animal Husbandry, Faculty of Agriculture,University of Lampung. The eggs was produced by Isa Brown at 60 weeks old laying period. Average weight of the eggs was 60.52±1.31 g and coefficient of variation 2.16%. The research was designed by Complete Randomized Design with four treatments and five replications for every treatment. The treatments were P0 (control,without coating), P1 (coating by 50 % Aloe vera, 25 % MPS, 25% RF), P2 (coating by 40% Aloe vera, 30% MPS, 30% RF), P3 (coating by 30% Aloe vera 30%, 35% MPS, 35% RF). Result of this research indicated that coating egg did not affect (P>0.05) on decreasing weight of egg (DWE),yolk egg index (YEI), haugh unit (HU), and pH. Average of DWE was 3.17±0.66 %, YEI 0.29±0.03, HU 47.14±10.71, pH 7.48±0.31. It could be concluded that treatment of coating egg with Aloe vera, MPS, and RF didn’t affect DWE, YEI, HU, and pH. Analyzed data observations used variant with 5% trust level and continued with Least Significant Difference Test. The results showed that coating eggs using Aloe vera, mangosteen peel solution, and rice flour had not significant effect (P>0.05) to percentage egg weight lost, the haugh unit, egg pH, and yolk index. Keywords : Interior quality of egg, Aloe vera, Mangosteen peel solution, Rice flour, Strain Isa Brown